Pengaruh Kesehatan dan Keselamatan Kerja (K3) serta Beban Kerja terhadap Kinerja Karyawan pada PT Pangan Makmur Saleh Famili Kabupaten Aceh Besar - Hazirah Angelia Fudhni; Tarmizi Gadeng; Tuwisna Tuwisna (Politeknik Kampar, 2025)
This study aims to examine the influence of Occupational Health and Safety (OHS) and workload on employee performance at PT. Pangan Makmur Saleh Famili in Aceh Besar Regency. Data was collected using questionnaires, and an associative method was employed to assess the impact of the independent variables (OHS and workload) on the dependent variable (employee performance), both individually and collectively. A census sampling technique was utilized, resulting in a sample of 40 employees from PT. Pangan Makmur Saleh Famili who agreed to participate as respondents. The findings indicate that, individually, both Occupational Health and Safety (OHS) and workload significantly affect employee performance at PT. Pangan Makmur Saleh Famili.